Of Monetary Policy Analysis and Output Shocks - Maskay, Nephil Matangi (NRB Economic Review, 2000)
Nepal and India are contiguous countries having a pegged exchange rate arrangement existing for forty years with virtually no restrictions on labor or capital mobility. However, empirical analysis suggest the levels of the Nepalese and Indian monetary base do not share a long term relationship. Conditioning the monetary policy variables by output shocks (i.e. by their respective economic structures) now show them to be cointegrated. This implies that a long-term monetary analysis using unconditional variables may be misleading.